2019
DOI: 10.1186/s12873-019-0272-z
|View full text |Cite|
|
Sign up to set email alerts
|

Atypical presentation of hemorrhagic shock in pregnancy: a case highlighting the developing field of emergency medicine in Israel

Abstract: Background: Occult hemorrhagic shock secondary to uterine rupture represents a true obstetric emergency and can result in significant morbidity and mortality for both the patient and the fetus. Multiparity and prior cesarean sections are known risk factors. Typically, these patients present late in gestation, often secondary to the physiologic stresses on the uterus related to contractions. This pathology is less common earlier in pregnancy and can often be overlooked in the acute setting. Case presentation: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Trauma surgeons can support obstetric providers with expertise in management of hemorrhagic shock, resuscitation, and definitive hemostasis. This aligns with increasing reports citing the benefits of resuscitative balloon occlusion of the aorta (REBOA) for obstetric patients with noncompressible hemorrhage 2–6 . Our hospital is a regionalized center for the care of women at high risk of peripartum hemorrhage, including those with placenta accreta spectrum (PAS).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Trauma surgeons can support obstetric providers with expertise in management of hemorrhagic shock, resuscitation, and definitive hemostasis. This aligns with increasing reports citing the benefits of resuscitative balloon occlusion of the aorta (REBOA) for obstetric patients with noncompressible hemorrhage 2–6 . Our hospital is a regionalized center for the care of women at high risk of peripartum hemorrhage, including those with placenta accreta spectrum (PAS).…”
supporting
confidence: 69%
“…This aligns with increasing reports citing the benefits of resuscitative balloon occlusion of the aorta (REBOA) for obstetric patients with noncompressible hemorrhage. [2][3][4][5][6] Our hospital is a regionalized center for the care of women at high risk of peripartum hemorrhage, including those with placenta accreta spectrum (PAS). As such, a multidisciplinary team was convened to develop a strategy for high-risk obstetric surgeries in accordance with the American College of Obstetricians and Gynecologists-Society for Maternal Fetal Medicine Obstetric Care Consensus for PAS.…”
mentioning
confidence: 99%
“…3 Several groups have reported superior outcomes with resuscitative endovascular balloon occlusion of the aorta (REBOA) as an adjunct to hemorrhage control during cesarean hysterectomy for PAS. [4][5][6][7][8][9][10][11][12] A meta-analysis of 731 PAS patients who underwent cesarean deliveries in which a REBOA catheter was used to occlude the infrarenal aorta, termed zone 3, found that these women experienced significantly less blood loss, received fewer transfusions, and achieved a higher rate of uterine preservation compared with other hemorrhage control strategies. 9 However, in the 11 studies pooled to generate this metaanalysis, there was no specific standard location of occlusion within zone 3 of the aorta.…”
Section: Questionsmentioning
confidence: 99%
“…There are several approaches available to decrease surgical blood loss during cesarean hysterectomy, including multivessel surgical ligation, temporary aortic clamping, multivessel embolization, and balloon occlusion of the aorta or iliac arteries 3 . Several groups have reported superior outcomes with resuscitative endovascular balloon occlusion of the aorta (REBOA) as an adjunct to hemorrhage control during cesarean hysterectomy for PAS 4–12 . A meta-analysis of 731 PAS patients who underwent cesarean deliveries in which a REBOA catheter was used to occlude the infrarenal aorta, termed zone 3 , found that these women experienced significantly less blood loss, received fewer transfusions, and achieved a higher rate of uterine preservation compared with other hemorrhage control strategies 9 .…”
mentioning
confidence: 99%
“…Spontaneous rupture has been reported after uterine artery embolization or in unscarred uterus as well. Maternal age has also been associated with increased risk(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%